Patologi Dalam Evaluasi Kebijakan Publik Di Kementerian Agama - Attan Navaron; Suparno Suparno (Universitas 17 Agustus 1945, 2023)
This type of personnel expenditure is one of the plans that needs to be calculated carefully because in personnel expenditure problems often occur minus or surplus budgets at the end of the year which result in not achieving proper reporting. The purpose of this analysis is to carry out an analysis of the occurrence of minus budgets in personnel spending and strategies to solve these problems using SWOT analysis. This analysis was carried out using a qualitative approach. The types of data used in this study are primary data types, namely observations and interviews during the Forum Group Discussion and secondary data types, namely documents, journals, financial reports and other data related to the problem being analyzed. The results of this study are as follows: 1) the placement of personnel expenditures for all work units in a district/city area is in the Secretary General's DIPA which can break the chain of minus budget problems evenly so that it makes it easier to solve problems, 2) the problem of adding tasks to the finance section can be done by improving the performance management of the financial section. Conclusion: the completion of the minus budget can be used by placing the employee budget in one work unit, 3) pathology in bureaucracy conducted in readiness of employee and lack of reward. Placement of the budget in a work unit must be followed by the consequences affected by the transfer so that it does not cause problems.